THE INFLUENCE OF PARENTAL CONTROL, PARENTAL MONITORING, PARENTAL WARMTH TOWARD COMPULSIVE BUYING MEDIATED BY PARENTAL KNOWLEDGE - Suwarno, Henky Lisan; Abednego, Felicia; Tjiptodjojo, Kartika Imasari (IJRDO - Journal of Business Management, 2017)
Consumer buying behavior problems are very common in the community. One of the problemsof buying behavior is compulsive buying, this behavior appears as a side effect for the person toresolve his personal problems or this as a solution to his personal problems. As a result, thesebehaviors often cause new problems for the person, they buy something that is not a necessity,debt-induced, and can cause bad psychological effects for the personn. There are several factors that cause this behavior, one of them is the lack of control of the family in supervising thebehavior of the child, also the declining relationship between parents and children because ofindividualistic value, and between parents and children to communicate only as necessary . Thiscan lead to compulsive buying behavior, because when teenagers face problems they do not finda place to solve problems at home, as a result they seek solutions outside the home and one of them by doing this compulsive buying behavior. In this study, the authors examine the influenceof parental control, parental monitoring, parental warmth toward compulsive buying with mediated parental knowledge. The method were used to test the influence of independentvariables on the dependent variable using path analysis. Number of samples collected 904 respondents. The results of the study found positive effects of parental monitoring, parental control and parental warmth on parental knowledge. In this study also found the positiveinfluence of parental monitoring, parental warmth to compulsive buying, while for parentalcontrol does not affect the compulsive buying. The last result of the hypothesis testing found noeffect of mediation from parental knowledge in relationship between parental monitoring,parental control, parental warmth and compulsive buying